Women's solidarity initiatives in promoting rural social enterprises in the Philippines - Geges, Dhino B.; Torio, Diana (2018)
This study aimed to determine women’s solidarity initiatives in promoting rural social enterprises in disaster-prone community. The research used a case study approach and data were gathered through survey, key informant interviews, and community observation. Longwe’s (1995) empower-ment framework was employed as a guide in articulating how gender influences the emergence and development of social enterprise initiatives in the context of disaster management.

The study found that majority of the respondents were women, aged 30-39 years old (40%), married (78%), worked as rural farmers (50%), with household size of five (30%), and some belonged to an ethnic group (26%). Less than half of them (34%) attended elementary education and many had a monthly income of Php 1,000-3,000.00 only (42%). Research findings confirmed that SEs have emerged as a response to flooding incidence, which also resulted in the implementation of Marikina Watershed Rehabilitation program. Social enterprises were incubated by TSKC in collaboration with public and private sectors. The stages of women’s empowerment are reflected in the development and growth of these enterprises which include welfare, access, conscientization, mobilization, and control. Likewise, women were perceived as effective leaders in managing the organization (80%). Additional equipment (84%) and technical trainings (78%) were identified to be significant, especially for new women members engaged in reforestation and livelihood activities. Organizational member- ship can be further enhanced to encourage more indigenous people to participate and be helpful by sharing their indigenous knowledge in sustaining economic and environmental commitment.
Keywords: Women in rural development -- Philippines; Social enterprises